Puts the magic back into life: Fathers' experience of planned home birth. Issue 2 (June 2015) - Sweeney, Siobhan; O'Connell, Rhona
Abstract Background In Ireland, planned home birth is seen as an alternative but safe choice of maternity care. Women's experience of home birth is reported as positive but little is known about fathers' thoughts and feelings about planned home birth. Aim The aim of the study was to explore fathers' experience of planned home birth. Method Hermeneutic phenomenology was selected to explore the experiences of eight fathers whose partners had a recent planned home birth. Data were analysed using Interpretative Phenomenological Analysis (IPA). Results Themes identified were 'negotiating the decision', 'ownership of the birth' and 'changed way of being'. Fathers overcame their initial reservations about home birth before the decision to plan a home birth was agreed. They were actively involved with their partner in labour which gave themselves a sense of ownership of the experience and a valued post-birth intimacy. Their belief in natural birth was reaffirmed and the experience gave them a new perspective on life. Conclusion When men have a positive experience of childbirth they benefit personally and emotionally. This experience can strengthen their relationship with their partner and the family. Midwives are ideally placed to involve fathers actively in birth either in a home or hospital setting.